1992
DOI: 10.1128/mcb.12.12.5801
|View full text |Cite
|
Sign up to set email alerts
|

Mutations activating the yeast eIF-2 alpha kinase GCN2: isolation of alleles altering the domain related to histidyl-tRNA synthetases.

Abstract: The protein kinase GCN2 stimulates expression of the yeast transcriptional activator GCN4 at the translational level by phosphorylating the a subunit of translation initiation factor 2 (eIF-2a) in amino acid-starved cells. Phosphorylation of eIF-2a reduces its activity, allowing ribosomes to bypass short open reading frames present in the GCN4 mRNA leader and initiate translation at the GCN4 start codon. We describe here 17 dominant GCN2 mutations that lead to derepression of GCN4 expression in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
157
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(174 citation statements)
references
References 64 publications
13
157
0
4
Order By: Relevance
“…In this report, we provided several lines of evidence demonstrating that the 3AT s phenotype conferred by YIH1 overexpression results from dissociation of the GCN1-GCN2 complex and consequent impaired activation of GCN2. First, we showed that overexpression of YIH1 can suppress the growth defect conferred by a constitutively activated form of GCN2 that inhibits general translation initiation by high level phosphorylation of eIF2␣ (33). This result provides strong genetic evidence that YIH1 overexpression specifically inhibits GCN2 function.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this report, we provided several lines of evidence demonstrating that the 3AT s phenotype conferred by YIH1 overexpression results from dissociation of the GCN1-GCN2 complex and consequent impaired activation of GCN2. First, we showed that overexpression of YIH1 can suppress the growth defect conferred by a constitutively activated form of GCN2 that inhibits general translation initiation by high level phosphorylation of eIF2␣ (33). This result provides strong genetic evidence that YIH1 overexpression specifically inhibits GCN2 function.…”
Section: Discussionmentioning
confidence: 67%
“…The Slg Ϫ phenotype of GCN2 c -E601K-E1591K is suppressed by deletion of GCN1 (33), suggesting that GCN2 c -E601K-E1591K requires GCN1 binding for its activation. Therefore, if overexpressed YIH1 disrupts GCN1-GCN2 interaction, it should reverse the Slg Ϫ phenotype associated with the GCN2 c allele.…”
Section: Overexpressed Yih1mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids pC2707, pC2708, pC2709, and pC2710 expressing PERK-R598E, PERK-D603R, the double mutant PERK-R598E,E603R, and PERK-K633R, respectively, were generated by using fusion PCR to introduce the appropriate mutations in pC2706. Plasmid p722 is a low copy number URA3 vector that expresses GCN2 from its native promoter (7). Site-directed mutagenesis of p722 was used to generate the plasmids pC2745, pC2746, pC2747, and pC2748 expressing GCN2-K628R, GCN2-R594D, GCN2-D598R, and GCN2-R594D,D598R, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, growth on medium containing 3-AT is a simple test for eIF2␣ kinase activity in yeast. In contrast, high level phosphorylation of eIF2␣ by mutationally activated forms of GCN2 impairs general translation initiation in yeast and results in a slow growth phenotype (3,7). Whereas yeast cells lacking GCN2 are unable to grow on medium containing 3-AT, low level expression of heterologous PKR or PERK kinases confers a 3-AT-resistant phenotype (8,9).…”
mentioning
confidence: 99%